Characterization of reflectarray antenna unit cell configurations for mm-wave design at 28 GHz - Khan, Sher Dali; Abbasi, Muhammad Inam; Mohd Ibrahim, Imran; Sulaiman, Noor Hafizah (2024)
This work outlines the development and evaluation of reflectarray antenna unit cells that resonate at a frequency of 28 GHz designed for mm-wave 5G communication systems. The study explores the use of various element forms as the unit cell design and analysis process. The research seeks to enhance the performance of the antenna by examining the impact of different parameters on bandwidth, reflection loss, and reflection phase characteristics. It has been demonstrated that the reflection loss can be used to characterize the reflectarray loss and bandwidth properties while the phase curves can be used for the analysis of phase errors as well as bandwidth of reflectarray antennas. Moreover, the study also provides a technique to obtain progressive phase distribution which is required to transform the unit cells into a periodic array.